Factors Affecting Employee Performance While Remote Working in Nepalese Organization - Budha, Khushbu (Nepalese Journal of Management, 2025)
This study examines the factors affecting employee performance while remote working in Nepalese organization. Employee performance is the dependent variable. The selected independent variables are working environment, technology and equipment, flexible time, work life balance, and salary. The primary source of data is used to assess the opinions of respondents regarding working environment, technology and equipment, flexible time, work life balance, salary, and employee performance. The study is based on primary data. The primary data were gathered from 132 respondents through questionnaires. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of factors affecting employee performance while remote working in Nepalese organization. The study showed a positive impact of working environment on employee performance. It indicates that supportive and positive working environment leads to increase in employee performance. Similarly, the study showed a positive impact of technology and equipment on employee performance. It indicates that use of high level technology and equipment leads to increase in employee performance. Likewise, the study also revealed a positive impact of work life balance on employee performance. It indicates that higher the work life balance, higher would be the employee performance. Further, the study observed a positive impact of flexible time on employee performance. It indicates that higher the flexible time, higher would be the employee performance. In addition, the study observed a positive impact of salary on employee performance. It indicates that higher the salary, higher would be the employee performance.